Twenty cases of allergic contact dermatitis due to benzoyl peroxide in acne patients in Japan - Shigeruko Iijima; Takahiko Tsunoda (Frontiers Media S.A., 2019)
Abstract Background Benzoyl peroxide is a topical antiacne drug, which also acts as a strong irritant and a weak allergen. Only a few acne patients with allergic contact dermatitis due to benzoyl peroxide gel have been diagnosed by patch testing in Japan. Therefore, the number of such patients is probably underestimated. Objectives To correctly diagnose such cases by patch testing and to determine their characteristics and frequency. Patients and methods Twenty acne patients that were diagnosed with allergic contact dermatitis between April 2015 and April 2018 were enrolled in this study. Patch tests were performed with acne gels containing benzoyl peroxide and 1% benzoyl peroxide in petrolatum. The patients' profiles and the frequency of dermatitis were analyzed. Results All of the patients were female, and their mean age was 24.1 ± 9.3 years. Two patients were suffering from atopic dermatitis. The onset of allergic contact dermatitis occurred at 1 to 2 days, 9 to 28 days, and >30 days (longest: up to 24 months) after the initial application of the causative substance in 3 patients, 9 patients, and 8 patients, respectively. The frequency of such cases was 4.5% at our clinic. Conclusions Benzoyl peroxide gels for acne were demonstrated to often act as allergic contact allergens, and thus, dermatologists should be aware of their allergenicity and be apprehensive about markedly increasing the use of such gels in the future.